Development of helical auxetic yarn with negative Poisson's ratio by combinations of different materials and wrapping angle. Issue 2 (June 2022) - Ullah, Tehseen; Ahmad, Sheraz; Nawab, Yasir
Auxetic materials have negative Poisson ratio which has a multiple ranges of functional applications. The helical auxetic yarn was successfully developed through direct twist system by using core and wrap yarn or filament, which shows Auxeticity when the HAY is stretched in longitudinal direction in response it expand in transverse direction, Helical Auxetic Yarns were developed using various parameters of the core and warp filament, these parameters are wrapping angle (Twist per meter), diameter ratio, and modulus ratio. The strength of Helical yarn was characterized using single yarn strength and Image J software was used for the calculation of poisson's ratio. According to test results, it is concluded that the core filament of helical auxetic yarn increased its thickness in transverse direction under stress, and a considerable negative poisson's ratio was calculated. The values of negative poisson's ratio described that the auxeticity had a direct relation with core filament thickness or diameter and inversely proportional to the linear density of wrap filament, in case of the wrap angle the auxeticity of HAY yarn had an inverse effect with wrap angle. Kevlar/polypropylene combination sample showed maximum auxeticity at a 15-degree angle while Kevlar/nylon combination sample showed minimum auxeticity at a 25-degree wrap angle.